Pengaruh Pengetahuan, Sikap, Dukungan Keluarga, Sarana Prasarana Dan Dukungan Guru Terhadap Kepatuhan Pola Hidup Sehat Bersih Di SMK SPP SNAKMA Muhammadiyah - Elpriska Elpriska (Pusat Riset dan Inovasi Nasional, 2022)
Healthy school children or Clean and Healthy Living Behavior (PHBS) in the school setting aims to cultivate PHBS for school children. The aim to be achieved in this research is to determine and analyze the behavior of school children regarding compliance with a clean and healthy lifestyle at SPP SNAKMA Muhammadiyah Vocational School. This type of research is a descriptive analytical survey with a cross sectional design. The research population was 132 high school level students. Sampling was taken using the total population method. Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that patient success influences knowledge, attitudes, family support, infrastructure and teacher support with a value of p = 0.000, meaning that there is an influence of knowledge, attitudes, family support, infrastructure and teacher support on adherence to a clean lifestyle. Healthy. From the results of the multivariate analysis, it is known that the most influential variable in this study is the family support variable with an OR value of 6.020. The research conclusion is that family support is the dominant factor influencing adherence to a clean and healthy lifestyle.